DDIS-18. NANOCELL-MEDIATED DELIVERY OF MIR-34A COUNTERACTS TEMOZOLOMIDE RESISTANCE IN GLIOBLASTOMA. (11th November 2019) - Babar Khan, Muhammad; Ruggieri, Rosamaria; Tran, Nhan; Sarkaria, Jann; MacDiarmid, Jennifer; Brahmbhatt, Himanshu; Boockvar, John; Symons, Marc
Abstract: BACKGROUND: Glioblastomas show marked intra- and inter-tumor heterogeneity and are strongly resistant to both radio- and chemo-therapy, which are standard therapeutic modalities for this tumor. MicroRNAs (miRNAs) have the potential to serve as effective therapeutics for glioblastoma as they modulate the activity of multiple signaling pathways. METHODS: Glioblastoma cultures were transfected with miR-34a or control miRNA mimics to assess biological function and therapeutic potential in vitro . miR-34a was packaged into bacterially-derived nanocells and administered intravenously for delivery to orthotopic patient-derived glioblastoma xenografts in mice. RESULTS: Overexpression of miR-34a strongly reduced the activation status of the three core signaling networks that have been found to be deregulated in the vast majority of glioblastoma tumors, the receptor tyrosine kinase, p53 and Rb networks. miR-34a transfection also inhibited the survival of multiple established glioblastoma cell lines as well as primary patient-derived xenograft cultures representing the proneural, mesenchymal and classical subtypes. Transfection of miR-34a synergized with temozolomide (TMZ) in in vitro cultures of glioblastoma cells with primary TMZ sensitivity, primary TMZ resistance and acquired TMZ resistance. Intravenous administration of bacterially-derived nanocells carrying miR-34a strongly enhanced TMZ sensitivity in an orthotopic patient-derived xenograft mouse model of glioblastoma. CONCLUSIONS: miR-34a strongly sensitizes a wide range of glioblastoma cell cultures to TMZ, suggesting that combination therapy of TMZ with miR-34a may serve as a novel therapeutic approach for the treatment of glioblastoma tumors. Bacterially-derived nanocells are an effective vehicle for the delivery of miR-34a to glioblastoma tumors.